NEW JERSEY EMPLOYMENT DISCRIMINATION BILL (Tufts Archival Research Center, 2007)
Marginalia; Letter to James Johnston from MB Oglesby and Roger Mozingo regarding the New Jersey Employment Discrimination Bill. Reports intended attempts to override Governor Jim Florio's veto of the bill and the numbers of votes required in both Houses to override the veto. Announces plans of industry lobbyists to introduce another version of an employment discrimination bill if the override doesn't pass. Mentions pressures on legislators by RJ Reynolds Tobacco Company.